Type 1 diabetes mellitus in the African population: epidemiology andmanagement challenges - Majaliwa, E. S.; Jerome Elusiyan, B. E.; Adesiyun, O. O.; Laigong, et al., P. (Acta Biomedica Atenei Parmensis, 2009)
Type 1 Diabetes Mellitus (T1DM) is a growing concern worldwide; while there has been a great improvement in the knowledge, epidemiology and management of this condition in the developed worlds, there has been little or no improvement in sub-Saharan Africa. The true burden of this disease is not even known, but a difference in the pattern and outcome of T1DM in the sub-Saharan Africa compared to the western World seems to be present. Moreover, much of the available data is not population-based and is of limited value for making generalizations about Diabetes in children of Sub-Saharan Africa. Despite the limitations, there is evidence that these populations may be important for studying the aetiology and natural history of Type 1 diabetes. Effective management and/or prevention of diabetes and its complications in Sub-Saharan African children should adopt multidisciplinary approaches. In order to improve care for diabetes patients in developing countries, specialized clinics need to be established.